COMPANY INCOME TAX AND ECONOMIC GROWTH IN NIGERIA - Odunsi, Oluwasegun Temitayo; Adeyemi, Adekunle Akeem; Okewale, Joel Adeniyi (Jurnal Ekonomi dan Bisnis Airlangga, 2025)
Introduction: This study evaluated the impact of company income tax revenue on Nigeria's economic growth. The ex post facto research design was employed for this investigation. Methods: This study utilized time series data, with information being gathered from the National Bureau of Statistics, the Federal Inland Revenue Service (FIRS) gazette, and the Central Bank of Nigeria (CBN) Statistical Bulletin for a period of thirty-two years, ranging from 1992 to 2023. The study employed the Ordinary Least Squares approach to evaluate the hypothesis, and the ARDL was used to determine the short- and long-term associations between the explanatory and dependent variables for this period. Results: The study's results for the hypothesis demonstrated that company income tax revenue (CITr) and gross domestic product have a positive relationship. The finding is significant at the 0.05 level (p < 0.05), suggesting that greater corporate taxes might boost economic growth by giving the government more money for services and public investments that will boost the economy. The results of the study indicated that company income tax revenue has a major impact on Nigeria's economic growth. Conclusion and suggestion: Consequently, the study recommended that the Government should ensure stability in Company Income Tax (CIT) policies to encourage investor confidence. In addition to that, CIT revenue should be strategically channeled into infrastructure, education, power supply, and industrial development. When taxpayers see tangible benefits, compliance improves, and economic growth is stimulated.